The Effectiveness of Topical Steroid Cream in the Management of Phimosis Developed Following Circumcision Performed With Thermocautery - (:unkn) unknown (My University, 2020)
Objective: In our country, thermocautery device is used extensively for circumcision per-formed under local anesthesia for fast and safe circumcision. One of the complications that may occur after circumcision with thermocautery is pathological phimosis. However, there aren’t stud-ies in the literature regarding the medical treat-ment of pathological phimosis after circumcision with thermocautery. We aimed to investigate the effectiveness of topical corticosteroid application in the treatment of pathological phimosis devel-oped after circumcision with thermocautery.Material and Methods: Data of 68 patients (aged: 1-8 years) who developed phimosis second-ary to circumcisions performed by one surgeon between the years 2009 and 2018 were analysed retrospectively from a computerised database. Cases of phimosis developed after circumcisions performed using thermocautery and scalpel were analysed in two separate groups, and the effective-ness of topical steroid treatment was evaluated.Results: In the thermocautery group, 32 pa-tients who developed Grade 5 phimosis didn’t respond to steroid therapy, while only three of 16 (18.75%) cases with Grade 4 phimosis responded partially to topical steroid treatment. All these 48 cases were treated with surgery. In the scalpel group, no therapeutic response was elicited in four cases who developed Grade 5 phimosis. Howev-er, four out of eight (50%) patients with Grade 4 and six out of eight (75%) patients with Grade 3 phimosis responded to steroid therapy, and full re-traction of the foreskin was achieved. In the scal-pel group, ten cases underwent surgical revision.Conclusion: Topical steroid creams may be partially beneficialin cases of pathological phimosis after circumcision. However, theydo not show efficacy in cases of high-grade phimosis after thermo-cautery use.

Amaç: Termokoter cihazı, hızlı ve güvenli sünnet için lokal anestezi altında yapılan sünnet-lerde ülkemizde yaygın olarak kullanılmaktadır. Termokoterle sünnet sonrası gelişebilecek komp-likasyonlardan bir tanesi de patolojik fimozdur. Ancak literatürde bu komplikasyonun medikal te-davisi ile ilgili çalışma yoktur. Termokoterle sün-net sonrası gelişen patolojik fimozisin tedavisinde topikal kortikosteroid uygulamasının etkinliğini araştırmayı amaçladık._x000D_ _x000D_ Gereç ve Yöntemler: 2009 ile 2018 yılları ara-sında, hastanemizde uygulanan sünnetler sonrası sekonder fimozis gelişen, yaşları 1-8 arasında de-ğişen 68 hastanın verileri bilgisayardan retrospek-tif incelendi. Termokoter ve bistüri kullanılarak yapılan sünnetlerden sonra gelişen fimozis vaka-ları iki ayrı gruba ayrılarak topikal steroid tedavi-sinin etkinliği değerlendirildi._x000D_ Bulgular: Termokoterle sünnet sonrası grade 5 fimozis gelişen 32 vaka da steroid tedavisine hiç-bir yanıt alınamadı. Grade 4 fimozis gelişen geli-şen 16 vakanın üç tanesinde kısmi yanıt alınsa da, bu 48 vakanın tamamına cerrahi düzeltme yapıldı. Bistüri grubunda ise grade 5 fimozis gelişen dört vakada da steroide yanıt alınamazken, grade 4 fi-mozis gelişen sekiz vakanın dört (%50) tanesinde ve grade 3 fimozis gelişen sekiz vakanın altı (%75) tanesinde steroide yanıt alınarak full retraksiyon sağlandı. Bu grupta toplam on vakaya cerrahi mü-dahale yapıldı._x000D_ _x000D_ Sonuç: Sünnet sonrası gelişen patolojik fi-mozis durumlarında da topikal steroid kremler kısmen fayda sağlayabilir. Ancak termokoter kul-lanımı sonrası gelişen yüksek dereceli fimozis va-kalarında etkinlik gösterememektedirler._x000D_
Termokoterle Yapılan Sünnet Sonrası Gelişen Fimozisin Tedavisinde Topikal Steroid Kremin Etkinliği